2018
DOI: 10.3389/fncel.2018.00348
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Delays Oligodendrocyte Progenitor Cell Migration and Myelin Formation by Suppressing Bmp2b Signaling in Larval Zebrafish

Abstract: Hypoxia in newborns tends to result in developmental deficiencies in the white matter of the brain. As previous studies of the effects of hypoxia on neuronal development in rodents and human infants have been unable to use in vivo imaging, insight into the dynamic development of oligodendrocytes (OLs) in the central nervous system under hypoxia is limited. Here, we developed a visual model to study OL development using sublethal postnatal hypoxia in zebrafish larvae. We observed that hypoxia significantly supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Previous reports have shown that hypoxia impairs the migration of OPCs [ 23 ]; however, not much is known about the effects of hyperoxia on the migration of OPCs and the molecular signalling involved. Therefore, in order to get a detailed insight into what happens to OPCs under hyperoxic conditions, we treated the OLN93 cells with 80% O 2 for a period of 24 hours without glucose or serum deprivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that hypoxia impairs the migration of OPCs [ 23 ]; however, not much is known about the effects of hyperoxia on the migration of OPCs and the molecular signalling involved. Therefore, in order to get a detailed insight into what happens to OPCs under hyperoxic conditions, we treated the OLN93 cells with 80% O 2 for a period of 24 hours without glucose or serum deprivation.…”
Section: Resultsmentioning
confidence: 99%
“…Myelination is achieved by extending many branched processes that wrap around the axon multiple times. But prior to the onset of myelination, newborn OL precursor cells (OPCs) undergo a phase of local proliferation followed by extensive migration to different parts of the brain from their point of origin [ 23 ]. Therefore, in a developing brain, proper myelination and remyelination are highly dependent on the capacity of OPCs to migrate to their target destinations and initiate differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly other contributing factors resulting from infection likely in uence glial responses. For instance, hypoxemia is known to affect developing OLs 69,70 . Possible underlying processes are enhanced systemic in ammation and increased oxidative stress that can also occur under hypoxic conditions caused by acute respiratory infection.…”
Section: Discussionmentioning
confidence: 99%
“…On one end, relatively higher oxygen tension seems to favour the growth of neurons and oligodendrocytes, with consequent increase in intracortical myelination, which is most pronounced at lower levels of the human cortical hierarchy (Burt et al, 2018). Relatively lower oxygen tension instead seems to rebalance the cell milieu away from myelinating oligodendrocytes and towards astrocytes (Xie et al, 2014, Yang et al, 2018 which support glucose transport and metabolism (Pellerin and Magistretti, 1994). Thus, by regulating the type of cells that develop in a given region, oxygen tension contributes to establish higher aerobic glycolysis at the top of the hierarchy, and higher myelination at the opposite (lower) end of the hierarchy.…”
Section: Non-allometric Cortical Expansion Induces Lower Oxygen Tensionmentioning
confidence: 99%